(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
Background: As rapid and precise detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in patient but there are limited data comparing sensitivity of saliva and nasopharyngeal swab (NPS) specimen for SARS-CoV-2 detection. Saliva is less invasive and more convenient for the patients. But NPS is the reference sampling method for the detection of SARS-Cov-2. Objective: It was aimed to compare the sensitivity specificity of nasopharyngeal saliva and saliva swab compared to for COVID-19 testing. Methodology: This cross-sectional study was conducted from 15 April to 30 April, 2021. One saliva sample and another NPS sample collected from 100 peoples and amplified using three different target genes (RdRP, N and E genes) by RT-PCR. Sensitivity, specificity and positive andnegative predictive values of Saliva swab was determined using NPS swab RT-PCR as the gold standard for diagnosis of COVID 19. Results: Among 100 people, 58 were men. The median age was 31 years. Among total patients most common symptoms were fever followed by sore throat and cough. The sensitivity and specificity of saliva samples were 91% and 100% respectively. Positive predictive value and negative predictive value were 100% and 88% respectively. An analysis of the agreement between the two specimens revealed 89% observed agreement (k coefficient 0.89, p < 0.001). Conclusions: Saliva can be an alternative sampling method in patients who cannot provide a NPS sample for the diagnosis of COVID-19. As this method is non-invasive, and non-aerosol generating, it can provide a good diagnostic performance. Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S20-S23